2010
DOI: 10.1227/01.neu.0000365263.14725.39
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Intracranial Temozolomide With Intracranial Carmustine Improves Survival When Compared With Either Treatment Alone in a Rodent Glioma Model

Abstract: The survival of tumor-bearing animals in the 9L and F98 glioma models was improved with the local delivery of BCNU and TMZ combined with XRT when compared with either treatment alone or oral TMZ, local BCNU, and XRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 28 publications
0
37
0
Order By: Relevance
“…Glioblastoma multiforme (GBM), the most common and aggressive form of brain malignancies, remains mostly incurable and has about 1-year median survival postdiagnosis, despite considerable advances in diagnosis, therapies, and understanding of its molecular pathways (1)(2)(3)(4)(5). Recent studies have revealed that a cancer-cell subpopulation in brain tumors-glioma stem cells (GSC)-exhibits tumor-initiating ability, self-renewal, and aberrant differentiation and is responsible for glioma initiation and progression (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Glioblastoma multiforme (GBM), the most common and aggressive form of brain malignancies, remains mostly incurable and has about 1-year median survival postdiagnosis, despite considerable advances in diagnosis, therapies, and understanding of its molecular pathways (1)(2)(3)(4)(5). Recent studies have revealed that a cancer-cell subpopulation in brain tumors-glioma stem cells (GSC)-exhibits tumor-initiating ability, self-renewal, and aberrant differentiation and is responsible for glioma initiation and progression (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Intracranial delivery of temozolomide (TMZ) polymers was found to be superior to oral administration in a gliosarcoma rat model [61] and was suggested to be well tolerated in humans [62,63]. Local delivery of TMZ and carmustine improved the survival of tumor-bearing animals in the 9 L and F98 glioma models [64]. Even by local delivery, systemic toxicity due to diffusion from the tumor site is a possibility.…”
Section: Discussionmentioning
confidence: 99%
“…2a-b). Long-term survivors were defined as animals that survived for more than 120 days following 9L cell implantation [35]. Magnetic resonance imaging [36] …”
Section: Importance Of the Administration Route On The Activity Gradientmentioning
confidence: 99%